(untitled) (Религиски дијалог и соработка, 2021)
The primary aim of this paper is to present and explain the concept of peace and unity from the perspective of Orthodox Christianity. Its core comprises the testimony of Christ’s love in this world, as an utmost Christian ideal, based on Christ’s commandment of love towards enemies and not repaying evil with evil but rather with goodness and love, as the basic principles of the Christian martyric ethos and pathos. This study is descriptive and describes the concept of peace and unity as essential Orthodox postulates in the context of the Orthodox theology according to the canon law, liturgical life and most importantly—the ascetic-hesychastic practice of the Holy Fathers of the Church and monasticism. The following terms are used: metanoia, Christian identity, pastoral approach (defined by the author), as well as the differences between theocentric and anthropocentric life models with various forms of social organization and identification. Thus, it offers a different perspective and implementation via an applicable model that springs from the liturgical life of the Church, which is to be set as a social example. The Church’s principles of peace and unity implemented in the everyday life of each person should contribute to a higher level of awareness, responsibility and social welfare, whereas each person should be an axis uniting people and should take the role of a peacemaker.